Climate and land-use change during the late Holocene at Lake Ledro (southern Alps, Italy). (HoloceneHolocene, 2014)
This paper investigates the relative influences of climatic and anthropogenic factors in explaining environmental and societal changes in the southern Alps, Italy. We investigate a deep sediment core (LL081) from Lake Ledro (652 m a.s.l.). Environmental changes are reconstructed through multiproxy analysis, that is, pollen-based vegetation and climate reconstruction, magnetic susceptibility (MS), lake level, and flood frequency, and the paper focuses on the climate and land-use changes which occurred during the late Holocene. For this time interval, Lake Ledro records high mean water table, increasing amount of pollen-based precipitation, and more erosive conditions. Therefore, while a more humid late Holocene in the southern Alps has the potential to reinforce the forest presence, pollen evidence suggests that anthropogenic activities changed the impact of this regional scenario. Land-use activity (forest clearance for pastoralism, farming, and arboriculture) opened up the large vegetated slopes in the catchment of Lake Ledro, which in turn magnified the erosion related to the change in the precipitation pattern. The record of an almost continuous human occupation for the last 4100 cal. BP is divided into several land-use phases. On the one hand, forest redevelopments on abandoned or less cultivated areas appear to be climatically induced as they occurred in relation with well-known events such as the 2.8-kyr cold event and the ‘Little Ice Age’. On the other hand, climatically independent changes in land use or habitat modes are observed, such as the late-Bronze-Age lake-dwellings abandonment, the human population migration at c. 1600 cal. BP, and the period of the Black Death and famines at 600 cal. BP. [ABSTRACT FROM PUBLISHER]